OS 36-02 ASTRAGALOSIDE IV AMELIORATED MITOCHONDRIAL OXIDATIVE STRESS IN HYPERTENSIVE MICE WITH CARDIOMYOPATHY BY REGULATING MITOCHONDRIAL Ca2+ FLUX. (September 2016) - Wang, Qiongying; Xie, An; Xu, Han; Yu, Jing
Abstract : Objective: Abnormal Ca 2+ handling is thought to be related with triggered activity and mitochondria participate in Ca 2+ homeostasis. We evaluated the contribution of Astragaloside IV (ASI) for mitochondrial ROS and Ca 2+ Flux to cardiac function by using DOCA-salt hypertensive mice. Design and Method: We used the deoxycorticosterone acetate (DOCA)-salt mouse model. The ventricular myocytes isolated from mice was utilized for action potentials (APs) recording, potassium and L-type Ca 2+ currents. While we measured mitochondrial ROS monitoring with confocal microscopy and the changes in cytoplasmic and mitochondrial Ca 2+ by fluorescent imaging using Fluo-4 and Rhod-2. The heart tissue was used for the level of Na + -Ca 2+ exchange (NCX) protein measurements by western blotting. Results: The left ventricular volume was significantly enlarged, and the ejection fraction was reduced in cardiomyopathic mice of hypertension. Myocytes showed a decreased Ca 2+ transients and a significant increase in the AP duration at 90% repolarization from 83.4 ± 21.1 to 242.3 ± 43.3 ms, explained by augmented L-type Ca 2+ current and decreased total K + currents. Treatment of myocytes with ASI restored AP duration at 90% repolarization cardiomyopathic mice. Compared with the sham cells, the peak amplitudes (F/F0 ) of cytoplasmic Ca 2+ transients were reduced by 33% in myopathic ventricular cells. After external application of 50 μM ASI to cardiomyopathic cells, the peak amplitudes of cytoplasmic Ca 2+ transients enhanced from 2.56 ± 0.38 to 6.10 ± 0.85. The mitochondrial ROS overproduction was observed in myocytes of cardiomyopathic mice and reduced with ASI treatment. The level of NCX was decreased in the cardiomyopathic mice compared with the sham mice (p = 0.016), however, ASI improved the NCX level. Conclusions: Mitochondrial Ca 2+ handling and ROS play an important role in cardiomyopathy. The scavenging mitochondrial ROS by ASI might be beneficial in the setting of hypertensive cardiomyopathy. The antioxidantive effects of ASI in heart failure may be related to regulate the mitochondrial Ca 2+ Flux.